Moderasi Beragama dalam Film Animasi Upin & Ipin Episode ‘Indahnya Syawal’: Analisis Wacana Kritis Model Teun A. Van Dijk - Rial Sukma Hasibuan; Uky Firmansyah Rahman Hakim; Dahmul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the representation of religious moderation values in the “Indahnya Syawal” episode of the Upin & Ipin animation series. The background of this research is based on the importance of religious moderation in multicultural societies, especially in the digital era, which is filled with diverse streams of information that may potentially trigger social conflict if not addressed wisely. Animated media plays a strategic role in conveying social and religious messages, particularly to children as the next generation. This research employs a descriptive qualitative approach using the critical discourse analysis model of Teun A. van Dijk. The data were obtained from dialogues, storylines, and visual elements in the episode. The findings indicate that the values of religious moderation are represented through tolerance, togetherness, and mutual respect. Tolerance is reflected in scenes of mutual forgiveness, togetherness is shown through social interaction and visiting traditions, while respect is demonstrated through behaviors that honor elders and others. These values are constructed through simple dialogues, an educational storyline, and easily understood visual symbols. This study is expected to contribute to communication and da’wah studies, as well as to the utilization of animation as a medium for conveying moderate and tolerant religious messages more broadly